Rho-Kinase Inhibition Improves the Outcome of Focal Subcortical White Matter Lesions. Issue 7 (3rd June 2022) - Aykan, Sanem A.; Xie, Hongyu; Zheng, Yi; Chung, David Y.; Kura, Sreekanth; Han Lai, James; Erdogan, Taylan D.; Morais, Andreia; Tamim, Isra; Yagmur, Damla; Ishikawa, Hidehiro; Arai, Ken; et al.
Abstract : Background: Subcortical white matter lesions are exceedingly common in cerebral small vessel disease and lead to significant cumulative disability without an available treatment. Here, we tested a rho-kinase inhibitor on functional recovery after focal white matter injury. Methods: A focal corpus callosum lesion was induced by stereotactic injection of N 5 -(1-iminoethyl)-L-ornithine in mice. Fasudil (10 mg/kg) or vehicle was administered daily for 2 weeks, starting one day after lesion induction. Resting-state functional connectivity and grid walk performance were studied longitudinally, and lesion volumes were determined at one month. Results: Resting-state interhemispheric functional connectivity significantly recovered between days 1 and 14 in the fasudil group ( P <0.001), despite worse initial connectivity loss than vehicle before treatment onset. Grid walk test revealed an increased number of foot faults in the vehicle group compared with baseline, which persisted for at least 4 weeks. In contrast, the fasudil arm did not show an increase in foot faults and had smaller lesions at 4 weeks. Immunohistochemical examination of reactive astrocytosis, synaptic density, and mature oligodendrocytes did not reveal a significant difference between treatment arms. Conclusions: These data show that delayed fasudil posttreatment improves functional outcomes after a focal subcortical white matter lesion in mice. Future work will aim to elucidate the mechanisms.